A C126R de novo Mutation in CYBB Leads to X-linked Chronic Granulomatous Disease With Recurrent Pneumonia and BCGitis - de Albuquerque, Jose Antonio Tavares; de Oliveira Junior, Edgar Borges; Zurro, Nuria Bengala; Vendramini, Paola; Ishizuka, Edson Kiyotaka; Borgli, Daniela de Souza Paiva; de Souza, Monica Soares; Condino-Neto, Antonio (Frontiers in Pediatrics, 2018)
Chronic granulomatous disease (CGD) is an innate immune deficiency of phagocytic cells that results from mutations affecting the components of the NADPH oxidase system and impairs the production of reactive oxygen species. Patients with CGD are susceptible to recurrent infections and hyperinflammatory responses. Mutations in CYBB lead to the X-linked form of CGD and are responsible for approximately 70% of cases. In this study, we report the case of a 2.5-year-old male patient with recurrent pneumonia and Bacillus Calmette-Guérin infection (BCGitis). He presented with bullous impetigo at 18 days of age as his first clinical manifestation, which was followed by recurrent pneumonia and regional BCGitis. Genetic analysis revealed a novel de novo mutation in the CYBB gene in exon 5, which was a single nucleotide substitution c.376T>C leading to a C126R residue change.